In silico Analysis of Immunologic Regions of Surface Antigens (Sags) of Toxoplasma gondii - Alibakhshi, Abbas; Bandehpour, Mojgan; Nafarieh, Tina; Gheflat, Shivasadat; Kazemi, Bahram (Novelty in Biomedicine, 2017)
Background: Surface antigens (SAGs) of Toxoplasma gondii are known candidates for diagnostic tests and vaccines. The present study argues about the main necessary properties for determination and prediction of T-cell agretopes and B-cell epitopes of surface antigens of Toxoplasma gondii. Materials and Methods: Primary, secondary and tertiary structures of the proteins were analyzed by different methods. The three-dimensional structures were determined by use of ab initio method for prediction of discontinues epitopes. The agretopes and epitopes were predicted via several various web servers with different methods employed. Results: The results of in silico analyses showed that the regions 129-GAPAGRNNDGSSAPT-143 for protein p22, 234-SENPWQGNASSD-245 for protein p30 and 348-PGTEGESQAGT-358 for protein p43, have the highest immunogenic potential. Conclusion: We reached to three antigenic epitopes for cloning and protein expression. In following the purified polypeptide will be applied for diagnosis of Toxoplasma gondii.